Analisis Strategi Pemasaran Pada Organisasi Dekranasda di Kabupaten Samosir - Wiranto Silalahi; Wesley Franklin Situmorang; Muhammad Ikhsan; Osberth Sinaga (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to analyze the marketing strategy implemented by the Regional National Crafts Council (DEKRANASDA) in Samosir Regency in developing local craft products and enhancing their competitiveness. This research employs a qualitative approach with data collection techniques through interviews, observation, and documentation. The findings reveal that DEKRANASDA has applied the elements of the marketing mix, including product, price, place, and promotion. However, several significant challenges persist, particularly in terms of limited promotional media and intense market competition. One major obstacle is the insufficient utilization of digital media as a marketing tool, which results in a limited market reach. Furthermore, product innovation needs to be improved to better align with consumer preferences and current market trends. Therefore, this study recommends that DEKRANASDA develop a digital-based marketing strategy, such as utilizing social media, e-commerce platforms, and an official website to enhance promotional reach. Additionally, innovation in design, raw materials, and product variations should be undertaken to attract consumers and compete in a broader market. This research provides important insights into the development of more effective marketing strategies to increase the income and competitiveness of craft products in Samosir Regency.